Endophytic Fungus Trichoderma asperellum's Virulence on Spodoptera frugiperda J. E. Smith (Lepidoptera, Noctuidae) Eggs - Ayubi Alfasiri; Trizelia Trizelia; Nurbailis Nurbailis (Jurnal Ilmu Pertanian Indonesia, 2025)
Spodoptera frugiperda J.E. Smith, sometimes known as armyworm, is a serious pest in maize crops. This pest affects maize plants' leaves, resulting in yield losses of up to 79.9%. Entomopathogenic fungi is one alternate method for controlling the pest. Various entomopathogenic fungus can be found in nature, one of which thrives endophytically on plants, such as Trichoderma asperellum. The purpose of this study was to obtain and evaluate T. asperellum's pathogenicity in suppressing S. frugiperda eggs. This investigation used five T. asperellum isolates (A116, PC21, S2D11, SD34, and AB2B3) obtained from diverse plant tissues. S. frugiperda larvae were treated with 2 mL of a conidia suspension containing 108 conidia/mL and sterile distilled water as a control. The observation variables comprised S. frugiperda egg mortality, first-instar larvae mortality, pupae formation percentage, and imago formation percentage. The findings indicated that the endophytic fungus T. asperellum can infect S. frugiperda eggs. The mortality rate for S. frugiperda eggs ranged from 43.27 to 78.34%. The mortality rate of first instar larvae ranged between 36.94% and 60.22%. The application of T. asperellum to S. frugiperda decreased pupae and imago production by 39.78% and 37.87%, respectively. T. asperellum SD324 is the most effective isolate for infecting S. frugiperda eggs. Keywords: endophytes fungus, entomopathogenic fungus, larvae, maize, Spodoptera frugiperda